Wpływ informacyjnych i komunikacyjnych technologii (IKT) na zmiany kierunków strategii małych i średnich przedsiębiorstw - Gierczak, Agata (Influence of Information and Communication Technologies (ICT) on Changes of Strategies Directions Used by Small and Medium Enterprises, 2006)
The aim of the article is to show relationship between used technologies, company's innovation and possibility to gain continuous competitive advantage on international markets. Sector of Small and Medium Enterprises is regarded as third area, apart from big companies, scientific-research units able to implement innovative solutions. Change in the direction of used strategies aims to modernise Polish companies and to increase effectivness of competing on international market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 260-266